Modeling the Psyche: Nene Humphrey's Multisensory Enactment of Empathetic Entanglement. - Albu, Cristina (Afterimage, 2017)
The article reviews an exhibition of art installations by artist Nene Humphrey at the Lesley Heller Workspace Gallery in New York, which includes the installations "Medieval Landscape," "Circling the Center" and "Pieces of Light".